2014
DOI: 10.1177/1367006913516042
|View full text |Cite
|
Sign up to set email alerts
|

The role of discourse context frequency in phonological variation: A usage-based approach to bilingual speech production

Abstract: Missing from the body of literature on contact-induced phonological influence are studies that examine language variation as it occurs in speech production among members of a speech community. This study uses a corpus of naturally occurring Spanish/English code-switched discourse to determine whether cross-language phonological effects are evident in the data. Specifically, 2629 tokens of word-initial /d/ were analyzed in spontaneous interactions to identify the linguistic factors that condition the variable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Similarly, a word that tends to occur in formal contexts, which disfavor reduction (e.g., the passive BE), might accumulate nonreduced pronunciations and thus be less subject to reduction even in contexts that are reductionfavoring (Torres Cacoullos 1999). Thus in creasing frequency may not favor reduction if the frequency increases come from reductiondisfavoring contexts (see also Brown 2014;Raymond and Brown 2012).…”
Section: English Auxiliaries and Grammaticalization Theorymentioning
confidence: 94%
“…Similarly, a word that tends to occur in formal contexts, which disfavor reduction (e.g., the passive BE), might accumulate nonreduced pronunciations and thus be less subject to reduction even in contexts that are reductionfavoring (Torres Cacoullos 1999). Thus in creasing frequency may not favor reduction if the frequency increases come from reductiondisfavoring contexts (see also Brown 2014;Raymond and Brown 2012).…”
Section: English Auxiliaries and Grammaticalization Theorymentioning
confidence: 94%
“…We refer to it here as FRC 1 (cf. Brown, 2009:93–100; Brown, 2004:89–114, 2005, 2006, 2015; Brown & Raymond, 2012; Bybee, 2000, 2002; Raymond & Brown, 2012). Brown (2004) reported that word-initial /s/ in the colonial Spanish of northern New Mexico and southern Colorado is reduced four times more often in words that occur most often in a phonological context that favors reduction, even when the immediate phonological context is controlled for.…”
mentioning
confidence: 99%
“…Brown (2009) found a similar effect with word-final /s/ in Cali, Colombia, but only when measured in favorable phonological contexts. Brown (2015) reported that word-initial /d/ in bilingual Spanish-English speech is reduced most in high-FRC words and that differences in /d/ articulation between cognates and noncognates can be attributed to differences in rates of FRC.…”
mentioning
confidence: 99%
“…The reducing effect of frequency is known to affect Spanish intervocalic /d/ (Bybee, 2001;Díaz-Campos & Gradoville, 2011;Eddington, 2011), the variable under study, although some researchers find frequency to have limited (Solon et al, 2018) to no (Bedinghaus & Sedo, 2014) effect on their data. Brown (2015), studying spirantization in word-initial /d/, found no significant frequency effect, but rather found that the frequency a word had /d/ occurring in contexts favorable to spirantization influenced whether spirantization occurred when /d/ appeared in unfavorable contexts. Looking at Peninsular Spanish processes affecting word-final /d/, Hualde and Eager (2016) found no significant effect for lexical frequency in their sample.…”
Section: A Usage-based Account Of Spanish /D/ In Contact With Portuguesementioning
confidence: 99%